Shirt Movements in Interwar Europe: a Totalitarian Fashion - Juan Francisco Fuentes (Ler História, 2018)
The article deals with a typical phenomenon of the interwar period: the proliferation of socio-political movements expressing their “mood” and identity via a paramilitary uniform mainly composed of a coloured shirt. The analysis of 34 European shirt movements reveals some common features in terms of colour, ideology and chronology. Most of them were consistent with the logic and imagery of interwar totalitarianisms, which emerged as an alleged alternative to the decaying bourgeois society and its main political creation: the Parliamentary system. Unlike liberal pluralism and its institutional expression, shirt movements embody the idea of a homogeneous community, based on a racial, social or cultural identity, and defend the streets, not the ballot boxes, as a new source of legitimacy. They perfectly mirror the overwhelming presence of the “brutalization of politics” (Mosse) and “senso-propaganda” (Chakhotin) in interwar Europe.